Rural public administration in Bangladesh: some observations - Mashreque, Md. Shairul; Kabir Hossaien (2000)
Rural public administration represents various streams of development intervention at the local level. The organisation with well-defined sets of power and responsibilities steer the wheel of rural administration. Based on formalised arrangement such organisations are bureaucratically controlled rendering public services and supply inputs and logistics as delivery system. In the whole process of development administration at the local level the role of representative local government is found to be minimal. Union Parishad exists as a unit of planning and development at the grassroots. Yet, it doesn't have enough power to emerge as a viable representative local self-government. Another stream of rural public administration is internal village administration that very much shapes the mechanism of social control at the base under the leadership of traditional village elite. Observing the whole process of rural public administration it may be commented that participatory components of rural development are missing in real life operation. Bureaucratic elites and local leaders are dominant actors. The performances of promotional extension agencies are far from satisfactory owing to shortage of governance and lack of participative management. Realising the pitfalls of rural administration there is a need for policy shift and reorientation in existing structures of governance. - Reproduced
Keywords: Public administration - Bangladesh; Local government